COVID-19, hypertension and cardiovascular diseases: Should we change the therapy? (2020)
The coronavirus disease (COVID-19) has spread all around the world in a very short period of time. Recent data are showing significant prevalence of arterial hypertension and cardiovascular diseases (CVD) among patients with COVID-19, which raised many questions about higher susceptibility of patients with these comorbidities to the novel coronavirus, as well as the role of hypertension and CVD in progression and the prognosis of COVID-19 patients. There is a very limited amount of data, usually obtained from a small population, regarding the effect of the underlying disease on the outcome in patients with COVID-19. The evaluation of the treatment of these comorbidities at baseline and during COVID-19 is scarce and the results are conflicting. Hypertension and CVD, after the adjustment for other clinical and demographic parameters, primarily age, did not remain independent predictors of the lethal outcome in COVID-19 patients. Some investigations speculated about the association between the renin-angiotensin-aldosterone system (RAAS) and susceptibility to COVID-19, as well as the relationship between RAAS inhibitors and the adverse outcome in these patients. Withdrawing or switching RAAS inhibitors would have uncertain benefits, but it would definitely have many disadvantages such as uncontrolled hypertension, cardiac function deterioration and renal function impairment, which could potentially induce more complications in patients with COVID-19 than the infection of coronavirus itself. The aim of this review article was to summarize the prevalence of hypertension and CVD in patients with COVID-19, their influence on the outcome and the effect of treatment of hypertension and CVD in COVID-19 patients.